Hassle in the dispensary: pilot study of a proactive risk monitoring tool for organisational learning based on narratives and staff perceptions. Issue 6 (12th March 2011) - Sujan, Mark-Alexander; Ingram, Catherine; McConkey, Tony; Cross, Steve; Cooke, Matthew W
Abstract : Aim: To prototype a system for identifying and monitoring those organisational processes that give rise to latent conditions that can contribute to failures in a dispensary environment. Methods: A proactive risk-monitoring system was prototyped during a 9-month period within the dispensary at Hereford Hospital. The system is used to identify empirically a preliminary set of Basic Problem Factors through qualitative analysis of narratives submitted by pharmacy staff about problems they encountered during their daily work. These factors are monitored and rated based on staff perceptions elicited through a questionnaire. At the concept stage, the system idea was discussed at two stakeholder workshops to ensure plausibility. A Plan–Do–Study–Act approach was used to prototype the system and to evaluate the perceived usability and perceived completeness of the system. Results: After four Plan–Do–Study–Act cycles, staff were satisfied with the usability of the questionnaire and the choice of factors being monitored. In total, 11 Basic Problem Factors were identified from the narratives, 10 of which have been monitored over a period of 6 months using a questionnaire. The differences in staff perceptions were statistically not significant. The qualitative and quantitative results led to improvements that included a review of all IT equipment in the department and the clean-up of the work environment. Conclusion: A system for identifying and monitoring organisational processes that give rise to latent conditions that may contribute to failures was prototyped at the dispensary at Hereford Hospital. This contributes to the organisation's efforts towards creating a proactive safety culture.